2017
DOI: 10.1021/acs.jmedchem.6b01894
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-((3R,4R)-4-Fluoro-1-(6-((3-methoxy-1-methyl-1H-pyrazol-4-yl)amino)-9-methyl-9H-purin-2-yl)pyrrolidine-3-yl)acrylamide (PF-06747775) through Structure-Based Drug Design: A High Affinity Irreversible Inhibitor Targeting Oncogenic EGFR Mutants with Selectivity over Wild-Type EGFR

Abstract: Mutant epidermal growth factor receptor (EGFR) is a major driver of non-small-cell lung cancer (NSCLC). Marketed first generation inhibitors, such as erlotinib, effect a transient beneficial response in EGFR mutant NSCLC patients before resistance mechanisms render these inhibitors ineffective. Secondary oncogenic EGFR mutations account for approximately 50% of relapses, the most common being the gatekeeper T790M substitution that renders existing therapies ineffective. The discovery of PF-06459988 (1), an irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…Each inhibitor and probe pair ( 1 / 4 , 2 / 5 , 3 / 6 ) displayed similar potency for inhibition of phosphorylated EGFR (pY1068) in H1975 cells, which express L858R/T790M-EGFR, and equivalent intrinsic reactivity in a conjugation assay with glutathione (GSH) (Table S1). Moreover, competitive ABPP assays with probes 4–6 provided estimates of inhibitor 1–3 cross-reactivity with WT-EGFR, as measured in A431 cells, that matched those determined using pY1068-EGFR measurements (Table S2 and Figure S2A) and were generally consistent with other literature reports, where inhibitors 1 and 2 have been found to cross-react to a greater extent with WT-EGFR than inhibitor 3 (Planken et al, 2017). Finally, probes 4–6 showed much weaker labeling of WT-EGFR in A431 cells compared to probe 7 (Figure S2B), which was based on a second-generation inhibitor with potent WT-EGFR activity (Lanning et al, 2014).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Each inhibitor and probe pair ( 1 / 4 , 2 / 5 , 3 / 6 ) displayed similar potency for inhibition of phosphorylated EGFR (pY1068) in H1975 cells, which express L858R/T790M-EGFR, and equivalent intrinsic reactivity in a conjugation assay with glutathione (GSH) (Table S1). Moreover, competitive ABPP assays with probes 4–6 provided estimates of inhibitor 1–3 cross-reactivity with WT-EGFR, as measured in A431 cells, that matched those determined using pY1068-EGFR measurements (Table S2 and Figure S2A) and were generally consistent with other literature reports, where inhibitors 1 and 2 have been found to cross-react to a greater extent with WT-EGFR than inhibitor 3 (Planken et al, 2017). Finally, probes 4–6 showed much weaker labeling of WT-EGFR in A431 cells compared to probe 7 (Figure S2B), which was based on a second-generation inhibitor with potent WT-EGFR activity (Lanning et al, 2014).…”
Section: Resultssupporting
confidence: 87%
“…This limitation could explain, for instance, why some of the kinase off-targets reported previously for inhibitor 2 , such as FER and TNK2 (Planken et al, 2017) were not detected in our studies. Likewise, we only evaluated a single cell line in this study and additional off-targets reported will likely be uncovered by extending our chemical proteomic analysis to other cell/tissue types (e.g., some of the other reported kinase off-targets of inhibitor 2 – ERBB4, BMX, BTK, and TXK – show very low or negligible expression in H1975 cells (Barretina et al, 2012, Klijn et al, 2015)).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It has potent pre-clinical EGFR activity against the four common mutants (exon 19 deletion (Del), L858R, and double mutants T790 M/L858R and T790 M/Del), selectivity over wild-type EGFR [27]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, Ceftolozane is a cephalosporin antibiotic of the 5th generation [1], Tozasertib is a pan-Aurora inhibitor [2]. Polysubstituted derivatives of pyrazole can act as antibacterial [3][4][5][6], anti-inflammatory [3,7,8], cytostatic [2,9,10], anesthetizing [11], anticancer [12][13][14][15], antiepileptic agents [16][17][18] and as insecticides [19,20].…”
mentioning
confidence: 99%